THE DIFFICULTIES AND STRATEGIES OF THEACHING PRACTICE ENCOUNTERED BY PRE-SERVICE TEACHERS OF MICROTEACHING SUBJECT - veny indah irfayanti; Yahya Alaydrus; Dzul Fikri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Microteaching is one way to prepare pre-service teachers to teach perfectly when practicing teaching. However, in microteaching there are unexpected problems by pre-service teachers, such as procedural, managerial, psychological, instructional, and professional. From some of these problems the researcher has the aim of the study of enriching strategies and overcoming problems encountered by pre service teachers when teaching practice. The research study design of this study was descriptive qualitative. The population of the study was students of eight-semester in University of Islam Malang.The participant were 60 pre-service teachers. The instrument of the research was questionnaire and interview. The questions of the test were made by the researcher. For getting valid test, the text of the test was measured by using data triangulation. From the difficulties above, some of pre-service teachers getting problems in preparing mentally, teaching materials, and knowledge so that pre-service teachers feel nervous while in front of the class. Therefore, there are four strategies that suitable to deal the difficulties that encountered by pre-service teacher at UNISMA are cooperative learning, setting up classroom management, interesting media, student-centered. For future researchers who are interested in discussing teaching difficulties and the strategies used can add quantitative data to get more results of lecturer, students, and course that are detailed and support qualitative data.Keywords: Microteaching, Teaching Practice, Problem of Teaching Practice, Strategies used